Virtualizing the Cultural Heritage of Rock Art: the case of “Sector X” in Toro Muerto – Arequipa, Peru - Gonzales, Liz Magali (2020)
Toro Muerto (valley of the Majes River, Arequipa-Peru), being one of the biggest archaeological sites of Rock Art in the world, gathers an impressive amount of petrographs: within an area of 10 km2, have been registered 2584 rocks engraved with geometrical, zoomorphic and anthropomorphic representations. In 2017, during prospections for the execution of the Toro Muerto Archaeological Research Project (PIA-TM, its abbreviation in Spanish) in 2017 has been discovered a Hill with 92 petroglyphs in the extreme north of Toro Muerto, not studied yet (“Sector X”). In 2018, the sector was completely documented creating one of the most exclusive registers of the site. Each rock counts with a file, calibrated photographs, drawings and for some rocks even 3D models. Additionally geodesic data as well as photogrammetric data was collected, ortophotographs taken and 3D and tecnomorphologic models of the sector developed and some excavations realized. This article is a case study about the integral virtualization of the Rock Art Cultural Heritage of the aforementioned sector.